Superkonektory barw w świadomości językowej Polaków i Rosjan - Rodziewicz, Barbara (Przegląd Wschodnioeuropejski, 2022)
The article presents a comparative analysis of selected linguistic material from associative dictionaries of the modern Polish and Russian languages. The object of the analysis are the units of an inverted dictionary, forming the so-called nucleus of linguistic awareness, i.e. words that act as a reaction to at least a few headwords. The so-called colour superconnectors, i.e. words-reactions showing the maximum number of connections with various words-stimuli, colours with maximum associative power. The analysis of the structures of lexical connections of coloratives in the nucleus of the linguistic awareness of Poles and Russians proves their similarity both in terms of frequency and the scope of the lexical span.